A novel energy pile: The thermo-syphon helical pile. (August 2019) - Huang, Jie; McCartney, John S.; Perko, Howard; Johnson, Drew; Zheng, Chao; Yang, Qingwen
Highlights: An energy pile is proposed based on the principles of helical piles and thermo-syphon to harvest geothermal energy. The principles of thermo- and fluid-dynamics were reviewed to understand its behaviors. An analytical model was developed to assess the efficiency of heat transfer of the proposed energy pile. The internal stability of the new energy pile under operational pressure was confirmed to not be a major issue. Abstract: This study focuses on assessing the heat transfer rate and structural stability of a novel self-operating energy pile based on the principle of a thermo-syphon. Specifically, this new energy pile, referred to as a "thermo-syphon helical pile" (THP), is formed by pressurizing a hollow helical pile with carbon dioxide (CO2 ) to form a heat pipe, where spontaneous liquid-vapor phase change and natural convection inside the pile will facilitate self-operating heat transfer from the pile tip to the pile head. Based on the theories of heat transfer and fluid dynamics, a simplified analytical solution was developed to calculate the heat transfer rates within THPs with different geometries, which can be further converted into equivalent thermal conductivities. The results indicate that heat transfer within THPs is a function of the boundary temperature applied to the pile head, CO2 pressure, working fluid properties, and THP geometry. The results also revealed that the equivalent thermal conductivity of the THP is 1000 times higher than that of most metals due to the latent heat transfer of working fluid. An analysis of the structural stability of a THP under pressure indicates that bifurcation is not a problem if the ratio of the diameter to thickness of a THP is less than 90. While this analytical feasibility study demonstrates that THPs are a promising alternative for energy piles for both new and retrofitted buildings, future studies on soil-pile thermal and mechanical interaction under operational thermal gradients are needed to evaluate the range of heat transfer rates from the subsurface to a building when using a THP.